Grating based devices in polymer optical fibre - Kalli, Kyriacos; Dobb, Helen L.; Webb, David J.; Carroll, Karen E.; Komodromos, Michael; Themistos, Christos; Peng, Gangding; Argyros, Alexander; Large, Maryanne C J; Van Eijkelenborg, Martijn A.; Fang, Qi; Boyd, Ian W. (My University, 2006)
We describe recent research into devices based on fibre Bragg gratings in polymer optical fibre. Firstly, we report on the inscription of gratings in a variety of microstructured polymer optical fibre: single mode, few moded and multimoded, as well as fibre doped with trans-4-stilbenmethanol. Secondly, we describe research into an electrically tuneable filter using a metallic coating on a polymer fibre Bragg grating. Finally we present initial results from attempts to produce more complex grating structures in polymer fibre: a Fabry-Perot cavity and a phase-shifted grating.
Keywords: Bragg gratings; Diffraction gratings; Electricity; Microstructure; Polymers; Optical fibers